The Correlation between Occupational Health with Job Performance at Woman Worker with Dual Role - Ariana Sumekar; Soebijanto Soebijanto; Hadi Sutarmanto (Intelektual Pustaka Media Utama, 2016)
Work environment and workload factors in terms of occupational safety and health aspects may lead to health problems that have an impact on decreasing the ability of the workforce to work physically and debilitating mental acuity to think so will degrade performance. Performance degradation is also influenced by the presence of an unbalanced workload and work motivation. The purpose of this research was to know the relationship between occupational health with a performance that is controlled by the workload and motivation of working in a dual role those women workers at PT. Mataram Tunggal Garment Yogyakarta.This study was conducted at PT. Mataram Tunggal Garment Yogyakarta with cross-sectional design. The samples in this study were 86 female workers were taken by simple random sampling. Uses data collected questionnaires and interviews. Data analysis was performed with the Pearson product moment test, whereas the partial correlation analysis and multivariate linear regression with a significance of p < 0.05. The Results showed there was a significant relationship between occupational health with a performance that is controlled by the workload and work motivation. The motivation of working has the most effective contribution to performance. While the burden of households does not affect the performance of the woman worker with a double role in PT. Mataram Tunggal Garment Yogyakarta.